2007
DOI: 10.1177/0145482x0710101206
|View full text |Cite
|
Sign up to set email alerts
|

Project Magnify: Increasing Reading Skills in Students with Low Vision

Abstract: Students with low vision, including those with multiple disabilities, are entitled to a comprehensive educational program that includes services from professionals in the field of visual impairment. This program should encompass a range of specialists and services that enable the students to complete current and future tasks in school, at home, in the workplace, and in the community. In particular, students with low vision require appropriate assessment, instruction, and adaptations to facilitate visual effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…The available fulltext articles were screened on inclusion and exclusion criteria and assessed for eligibility. Together with articles identified through searches in reference lists of previously retrieved reviews and the gray literature, this resulted in 64 articles, describing 66 different studies (28 RCTs, 3,7,13,16,19,21,32, 33,39,47,50,54,56e58,61,62,66,69,72,78,83,85,93,98,111,121,124 18 non-RCTs, 1,2,6,11,15,20,27,35,44,51,55,65,74,75,82,89,96,104 and 20 before-after comparisons (BAs) 8 articles of McMahon and Kederis described 2 different studies. 57,58,70,71 The 66 included studies were published between 1964 and 2018, and 37 (56.1%) of them were published in the last decade (2008e2018) 1e3, 13,15,16,19e21,27,28, 30,32,33,35,39,40,43,46,51,54,62,65,69e71,73e75,78,82,83,85,89,91,96,98,104,110,111,124 ( Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The available fulltext articles were screened on inclusion and exclusion criteria and assessed for eligibility. Together with articles identified through searches in reference lists of previously retrieved reviews and the gray literature, this resulted in 64 articles, describing 66 different studies (28 RCTs, 3,7,13,16,19,21,32, 33,39,47,50,54,56e58,61,62,66,69,72,78,83,85,93,98,111,121,124 18 non-RCTs, 1,2,6,11,15,20,27,35,44,51,55,65,74,75,82,89,96,104 and 20 before-after comparisons (BAs) 8 articles of McMahon and Kederis described 2 different studies. 57,58,70,71 The 66 included studies were published between 1964 and 2018, and 37 (56.1%) of them were published in the last decade (2008e2018) 1e3, 13,15,16,19e21,27,28, 30,32,33,35,39,40,43,46,51,54,62,65,69e71,73e75,78,82,83,85,89,91,96,98,104,110,111,124 ( Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…57 Fourteen studies reported a cutoff criterion for visual acuity. 1,11,13,21,27,28,30,35,47,51,54,75,78,89 Slightly more often, studies reported the degree of visual impairment (e.g., severe visual impairment, legal blindness) or fulfillment of certain criteria for low vision (e.g., the criteria for low vision of the WHO or the ICD criteria). 1,6,16,20,39,40,44,50,56,62,69,75,90,93,96,104,110,111,121 In some cases, authors quantified the number of participants with a certain degree of visual impairment, that is, how many participants had visual impairment and how many participants were blind.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations